Effects of vanadium substitution on the electrical performance of amorphous SrBi2Ta2O9 thin-film capacitors - Kang, Min-Gyu; Cho, Kwang-Hwan; Nahm, Sahn; Yoon, Seok-Jin; Kang, Chong-Yun (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
The effects of vanadium substitution on the dielectric properties of amorphous SrBi2Ta2O9 (SBT) thin films have been investigated. Vanadium substitution at the Ta site exists in the V3+ valence state and acts as an acceptor, reducing the number of intrinsic oxygen vacancies and the leakage current of the amorphous SBT thin films. Furthermore, the dielectric properties are also improved. The leakage current values of the 92 and 31 nm thick SBTV thin-film capacitors were 8.8 nA cm(-2) and 0.62 mu A cm(-2) at 1 V, respectively. (C) 2014 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: LEAKAGE CURRENT; TEMPERATURE